La doctrina de la Drittwirkung der Grundrechte en la jurisprudencia de la Corte Interamericana de Derechos Humanos - Mijangos González, Javier (Teoría y Realidad Constitucional, 2007)
Through a study of the jurisprudence of the region over the last twenty years, it becomes possible to see that the CIDH has constructed an entire theory about the applicability of fundamental rights in relations between individuals in Latin America. Through this theory it has addressed the most important social problems in contemporary Latin American history, thus contributing to the transition to democracy for many countries in the region. The study will analyze the stages that the jurisprudence of the CIDH has passed through and which have led to the current criteria that this organization uses. The first stage consists of a series of rulings whose common denominator is the analysis of the obligation of respect and vigilance for fundamental rights by the states listed in article 1.1 of the American Convention on Human Rights. This principle, which is ever-present in its jurisprudence, brings the Inter-American Court to approaches that are similar to those proposed by the United States doctrine of state action, as it makes use of a good number of rulings made by the Supreme Court of the United States between 1960 and 1980. In the second stage, the importance originally placed on determining the characteristics of the agent who committed the violation of fundamental rights is replaced by a series of approaches in which the nature of the actual violation itself becomes the focus. In this phase, the Inter-American Court establishes the idea that the fundamental rights listed in the Convention are erga omnes obligations that are imposed not only in relation to the power of the State but also with respect to the actions of third-party individuals. Finally, the third stage in the evolution of the court’s jurisprudence is represented by the most pertinent case in this matter: Opinión Consultiva 18/03, requested by the United Mexican States regarding the legal status of immigrants. This resolution, which has established a trend up until today, definitively establishes the direct effectiveness of the fundamental rights in relations between individuals.